Life cycle assessment in Indonesia forestry sector: A scoping review - Budi Mulyana; Mohamed Hemida (Talenta Publisher, 2023)
Life cycle assessment (LCA) is a tool to analyze the environmental impact of the process of production or services. Forest provides enormous environmental benefits through ecosystem services, but some forest management activities (nursery, thinning, pruning, pest control, and harvesting) have produced some negative impacts, such as pollution from machine utilization, fertilizer and pesticide, and water consumption. Furthermore, this paper describes the application of LCA in the forestry sector in Indonesia. We used the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) approach to identify, screen, and inclusion the relevant articles. Identified 35 articles related to life cycle assessment in Indonesia's forestry sector, and only 11 articles were eligible for content analysis. The findings have shown that the research trend on LCA in the Indonesia forestry sector started in 2009, but since 2015 the number of publications has been relatively constant. The functional unit used in LCA varied (mass, energy, time, and area size). The system boundary also variedÂ from cradle to gate, gate to gate, and cradle to grave. The environmental impacts found in the articles were global warming potential, acidification, and eutrophication parameters. In conclusion, LCA has been applied in Indonesiaâ€™s forestry sectors (roundwood production, furniture industries, biomass and wood pellet production). We propose that the future research direction is specific research in the site forest operation, such as seedling production, forest maintenance, and forest harvesting activities. We also recommend a more varied research scope to elaborate the LCA in private forest and non-timber forest product processes.